Antifungal Activity of Noni (Morinda citrifolia) Leaf Extract against Cercospora capsici on Red Curly Chili Pepper (Capsicum annuum) In Vitro - Gunawan, Adriano; Nurbayani, Farah Arhusy; Arikah, Zian; Aditya, Fitra Ari; Purwantisari, Susiana (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the antifungal potential of noni leaf (Morinda citrifolia) extract at different concentrations in inhibiting the growth of Cercospora capsici, the causal agent of leaf spot disease in red curly chili pepper (Capsicum annuum). The study was conducted using a Completely Randomized Design (CRD) consisting of seven treatments, including noni leaf extract at concentrations of 20%, 40%, 60%, 80%, and 100%, a negative control (sterile distilled water), and a positive control (0.1% propineb). The research procedures included purification of the Cercospora capsici isolate, preparation of methanolic noni leaf extract, qualitative screening of secondary metabolites, and an in vitro growth inhibition assay using the poisoned food technique. The inhibition data were analyzed using one-way analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Qualitative phytochemical screening revealed that noni leaf extract contained alkaloids, phenols, flavonoids, saponins, tannins, and steroids. The inhibition assay showed that the antifungal activity increased with increasing extract concentration. The highest Percentage Inhibition of Radial Growth (PIRG) was observed in the 100% noni leaf extract treatment, with a value of 93.82 ± 0.56%, categorized as very strong inhibition. This value was higher than that of the positive control (0.1% propineb), which exhibited a PIRG value of 47.19 ± 2.52%. These findings indicate that noni leaf extract has strong antifungal activity against Cercospora capsici under in vitro conditions and has potential as a plant-derived antifungal agent. Further studies under in vivo and field conditions are required to confirm its effectiveness in controlling leaf spot disease of red curly chili pepper.